Fostering Brand Loyalty in Retail Fashion: Integrating Innovativeness and Brand Love Model - Pratiwi, Ida Ayu Rani; Darma, Gede Sri (Riviera Publishing, 2026)
This study examines the role of fashion innovativeness in fostering brand loyalty within the retail fashion sector, using Uniqlo as the case study. It aims to analyze how perceived quality, brand love, and customer satisfaction mediate the relationship between fashion innovativeness and brand loyalty. A quantitative approach with a causal-associative design was employed, and data were collected from 190 respondents in Bali through a structured questionnaire. The findings of this study indicate that Fashion Innovativeness has a positive and significant influence on Perceived Quality, Brand Love, Customer Satisfaction, and Brand Loyalty. Product innovation by Uniqlo, reflected in its modern design, high-quality materials, and casual yet trend-driven approach, enhances perceived quality and fosters positive emotional experiences among consumers. The results also demonstrate that Perceived Quality significantly affects Brand Loyalty, while Customer Satisfaction plays a crucial role in shaping Brand Love and customer loyalty. However, Brand Love does not fully mediate the relationship between fashion innovation and brand loyalty, suggesting that emotional attachment must be supported by consistent experiences and engaging loyalty programs to sustain long-term relationships. Mediation analysis further confirms that Perceived Quality and Customer Satisfaction serve as significant mediators linking fashion innovation to brand loyalty. Overall, this study emphasizes that consumer loyalty in the retail fashion industry is not solely driven by product innovation but also by satisfaction and perceived quality built through positive brand experiences.